Kecerdasan Emosional, Keseimbangan Kehidupan Kerja Terhadap Kinerja Pegawai - Noor Iffatin Nadhifah; Siti Imaniatul Muflihatin (Journal of Islamic Economics and Finance, 2023)
Employment service companies which are familiarly known as outsourcing in Indonesia have recently emerged a lot, one of the advantages of this company is that a company that needs additional workers in its company can quickly get workers according to the criteria desired by the company. Apart from that, the company also doesn't need to be bothered with things like employee recruitment. Companies that provide labor services to be employed by other companies that request labor or companies that provide workers